E-239 Intra-aneurysmal flow after treatment with the woven endobridge (WEB) measured by quantitative digital subtraction angiography. (4th August 2020) - Shah, K; White, T; Turpin, J; Teron, I; Katz, J; Woo, H
Abstract : Introduction: The Woven EndoBridge (WEB) is an intra-saccular flow-diverting device that is rapidly becoming popular in the treatment of wide-neck bifurcation aneurysms. However, several challenges remain, such as device compression, incomplete occlusion, and thromboembolic complications. Changes in intra-aneurysmal flow after the use of the WEB are not well understood and may be important in the performance of the device for aneurysm occlusion. The aim of this study was to characterize the degree of immediate aneurysm occlusion using color-coded quantitative digital subtraction angiography (DSA) after treatment with the WEB. Materials and Methods: We retrospectively reviewed records of 34 patients treated with the WEB between March 2019 and February 2020. Eight patients were excluded from analysis for the use of a concurrent stent or intra-luminal flow-diverter. Measurements of contrast transit times on DSA were calculated with syngo iFlow (Siemens Healthineers AG). Regions of interest were selected within the parent vessel immediately proximal to the aneurysm and within the aneurysm dome before and after treatment with WEB (figure 1). The ratio of aneurysm contrast transit time to parent vessel contrast transit time was obtained before WEB placement and immediately after WEB placement. Transit time ratios were also compared with pre- and post-Pipeline (PED) cases matched for aneurysm size. Results: Out of 26 aneurysms, 24 aneurysms demonstrated an increase in contrast transit time after WEB placement (2.06 s, p<0.05), as measured by iFlow analysis. The ratio of aneurysm-to-parent vessel contrast transit time increased significantly after treatment with WEB (1.02 vs. 1.61; p<0.01). Similarly, the ratio of contrast transit time increased after PED deployment (1.07 vs. 1.51; p<0.01), however the ratio increased significantly more after WEB when compared to PED (67% vs 40%; p<0.05). Average aneurysm size was similar between WEB cases (n=26) and PED cases (n=26) (128.2 mm 3 vs 165.1 mm 3, p=0.52). The average number of PED devices used per case was 2.2. Conclusions: High rates of immediate aneurysm contrast stagnation can be achieved with use of the WEB. As a flow-diverting device, the WEB offers a greater degree of immediate aneurysm occlusion than the PED. iFlow analysis provides a quantitative measure of post-treatment effect and could represent a predictive tool for successful long-term occlusion. Disclosures: K. Shah: None. T. White: None. J. Turpin: None. I. Teron: None. J. Katz: None. H. Woo: None.